Nietzsche, godfather of fascism? : on the uses and abuses of a philosophy - Golomb, Jacob; Wistrich, Robert S., 1945-2015 (Princeton University Press, 2002)
Nietzsche, the Godfather of Fascism? What can Nietzsche have in common with this murderous ideology? Frequently described as the "radical aristocrat" of the spirit, Nietzsche abhorred mass culture and strove to cultivate an Ubermensch endowed with exceptional mental qualities. What can such a thinker have in common with the fascistic manipulation of the masses for chauvinistic goals that crushed the autonomy of the individual? The question that lies at the heart of this collection is how Nietzsche came to acquire the deadly "honor" of being considered the philosopher of the Third Reich and whether such claims had any justification. Does it make any sense to hold him in some way responsible for hte horrors of Auschwitz?